An empirical study of factor contribute towards the change of Voting age policy in Malaysia / Anis Syahirah Anuwar and Nur A’fifah Ahmad Fairuz - Anuwar, Anis Syahirah; Ahmad Fairuz, Nur A’fifah (2022)
The purpose of the study was to determine the views of UiTM Seremban 3 students on the contributing factors contribute towards the change of voting age policy in Malaysia. This research was carried out between March and August of 2022. In order to collect data for this study, the convenience sampling technique is used. The study's findings showed four significant conclusions. The majority of respondents agreed that education, social media, and political are the factors that affect students UiTM Seremban 3 towards the change of voting age policy in Malaysia. As a result, our study is uniquely positioned to provide both theoretical and empirical contributions to the multi-domain literature, which includes educational and political literature.